Full Metal Jhacket - Derby, Matthew (21St Century Prose, 2014)
Following his celebrated debut collection Super Flat Times, Matthew Derby delivers a disturbing new set of stories that plunges us into a lonely heartland of misfits, outcasts, and would-be assassins who lurk in the shadows, searching for connection and meaning in all the wrong places